Survey and registration of the occurrence of leaf-cutting ants in grassland areas - Costa, Weslley Botura; Barboza, Augusto Roberto Dias; Lopes, Ana Daniela; Francisco, João Paulo (Scientia Agraria Paranaensis, 2022)
Leafcutter ants tend to adapt to the different climatic conditions, soil, and vegetation.They also have the particularity of attacking different cultures. The objective of this work was to survey and record the occurrence of leafcutter ants in 5 pasture areas located in the municipalities of Altônia, Iporã, and Cafezal do Sul, as well as to identify them at the genus level. The study areas were covered by the walking method, performing the geolocation of the anthills in order to verify the incidence of anthills, calculating the anthill areas, preparing maps of land use, and occupation and geolocation of the anthills, calculating the density and the spatial distribution of anthills. Across the 5 areas, 56.72 ha of pasture were sampled and the existence of anthills inside the properties was established. Totally, 55 anthills were sampled from which specimens were collected for identification at the genus level, which will be classifiedunder the genus Atta. The areas of the anthills vary from 0.26 m² to 97.34 m². The density of anthills ranged between 0.25 and 0.75 anthills ha-1and the spatial distribution obtained was I = 1.13. Of the 55 anthills, all belonging to the Atta genera, and different types of management related to the occurrence of leafcutter ants in the areas.On the basis of the evaluation of monitoring and georeferencing data, it was possible to record the occurrence of leafcutter ants in pasture areas in the cities of Altônia, Cafezal do Sul, and Iporã, which presented different distribution and density of nests. In all evaluation areas, the domain of the genus Atta was registered.